Handbook of counseling women - Keitel, Merle A.; Kopala, Mary (Sage Publications, 2003)
`Until recently, women's specific issues were largely ignored. For too many years research, counselling interventions, and public policy have neglected women's voices and stories. With persistence and vigilance we now see major changes in research and practice that focus on women and their issues. Psychology played a major role in these advances and The Handbook of Counseling Women is part of the giant step forward that psychology is making in promoting counseling of women that encompasses an understanding of the gender, social/economic, and cultural impact of being a woman today' - Norine G Johnson, President, American Psychological Association, 2001 The Handbook of Counseling Women addresses current theories, research, and issues relevant to the mental and physical well being of women. Edited by Mary Kopala and Merle A Keitel, this comprehensive volume is divided into three parts. Part One focuses on theoretical, sociocultural, biological, and developmental considerations. Part Two is devoted to assessment, diagnosis, and intervention. Part Three covers supervision, research, and ethics. Most chapters include case studies, recommendations for further reading, and resources for clients.